STUDI KASUS POLA ASUH ORANG TUA PADA ANAK YANG MENGALAMI GANGGUAN PERILAKU - Maulia, Delia Ayunda; Mutias, Alya Sabrina; Pratama, Faisal Yuda; Kurniawati, Devi Ayu (Journal of Professional Elementary Education, 2024)
Behavioral disorders, which are disorders of adjustment to the social environment caused by weak self-control, are the most common cases in children. 50% or more of children aged 4-5 years have exhibited some external conduct disorder syndrome that can develop into a permanent conduct disorder (Campbell, Coie &; Reid, in Bennett, Brown, Lipman, Racine, Boyle &; Offord, 1999). In Indonesia itself, although there is no definite number, there are quite a lot of children who can be said to have behavioral disorders. The purpose of this study was to conduct research related to the influence of parenting on the aggressive behavior of 4-year-olds who tend to fight and hit. The method used in this study is to use qualitative descriptive methods, and the data collection tools in this study are observation and interviews. Based on the results and discussion in this study, it can be concluded that behavioral disorders in children who often fight and like to hit others, one of which can be influenced by parental parenting as well as the process of imitation from parents because parents are modeling (imitation) for children